Animal models of ulcerative colitis and their application in drug research - Low D; Nguyen DD; Mizoguchi E (Dove Medical Press, 2013)
Daren Low,1 Deanna D Nguyen,1,2 Emiko Mizoguchi1,2 1Gastrointestinal Unit, Department of Medicine, 2Center for the Study of Inflammatory Bowel Disease, Massachusetts General Hospital and Harvard Medical School, Boston, MA, USA Abstract: The specific pathogenesis underlying inflammatory bowel disease is complex, and it is even more difficult to decipher the pathophysiology to explain for the similarities and differences between two of its major subtypes, Crohn's disease and ulcerative colitis (UC). Animal models are indispensable to pry into mechanistic details that will facilitate better preclinical drug/therapy design to target specific components involved in the disease pathogenesis. This review focuses on common animal models that are particularly useful for the study of UC and its therapeutic strategy. Recent reports of the latest compounds, therapeutic strategies, and approaches tested on UC animal models are also discussed. Keywords: inflammatory bowel disease, preclinical trials, emerging therapy